RACISM DISCOURSE: MUSLIM STEREOTYPE AND DISCRIMINATION IN THE NOVEL OF SAFFRON DREAMS - Nursyakillah Musakar; Tisna Prabasmoro; Amaliatun Salehah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Muslims in America again became a concern when the events of 9/11 occurred in 2001. Muslims who already have a negative image in the eyes of the West have strengthened again, especially when it is associated with the issue of terrorism. The stereotype of Muslims as a religious and cultural identity is echoing again. The aims of this research is to explain Muslim stereotypes in the novel Saffron Dream by Abdullah (2009). This researchy uses a qualitative descriptive method with sociology of literature approach. The result of this research is that in the novel Saffron Dreams, there are two forms of racism experienced by the main character: the stereotype that they (Muslims) are terrorists. The second is that the stereotype leads Arrisa into discrimination, leading to physical and verbal violence. Based on all the explanations in the previous discussion, one of the main conclusions drawn by the author is that the cause of the racist behavior accepted by Arrisa stems from bad prejudice against Muslims because of their religious and racial similarities with the terrorists in the 9/11 tragedy in America which claimed thousands of lives. Because these prejudices make Americans think that Islam is a religion that teaches the science of terror and that all Muslims are terrorists.